A carbon-based all-dielectric loss multi-component composite material and preparation method thereof
By preparing carbon-based fully dielectric loss multi-component materials, the combination of capsin-containing functional structure amide compounds and monosaccharides and binary copolymer microspheres is used to form an attached or embedded carbon sheet structure, which solves the problems of high density, narrow absorption frequency band and poor corrosion resistance of existing electromagnetic wave absorbing materials, and achieves efficient electromagnetic wave absorption performance and good chemical stability.
Patent Information
- Application Number
- CN202310698469.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-06-13
AI Technical Summary
The existing electromagnetic wave absorbing materials have problems such as high density, narrow absorption frequency band and poor corrosion resistance, which are difficult to meet the requirements of new absorbing materials for ‘thin, light, wide and strong’.
By using carbon-based fully dielectric loss multi-composite materials, by preparing multi-composite materials containing C, N, and O elements, using the combination of organic small molecule capsin-containing functional structure amide compounds and monosaccharides and binary copolymer microspheres, an attached or embedded carbon sheet structure is formed to achieve efficient electromagnetic wave absorption.
The material's absorption rate of electromagnetic waves reaches more than 90% in the frequency band of 2 to 40GHz, avoiding the problems of large density and poor corrosion resistance of metal-based absorbent materials, while maintaining the lightweight and chemical stability of traditional carbon materials.
Smart Images

Figure HDA0004282791930000011 
Figure HDA0004282791930000021
Abstract
Description
[Technical field]
[0001] The present invention belongs to the technical field of electromagnetic wave absorbing materials. More specifically, the present invention relates to a carbon-based all-dielectric loss multi-component composite material, and the present invention also relates to a preparation method of the multi-component composite material. [Background technology]
[0002] In the information age, electronic devices have brought convenience to our lives, but at the same time, the pollution caused by electromagnetic waves has become increasingly serious. Electromagnetic wave absorbing materials can suppress electromagnetic interference and avoid secondary electromagnetic pollution by converting incident electromagnetic energy into heat or other types of energy, so they have great potential in removing electromagnetic wave pollution. So far, people have been committed to preparing ideal electromagnetic wave absorbing materials with thin thickness, low density, wide effective absorption bandwidth, and large reflection loss.
[0003] According to the electromagnetic wave loss mechanism, absorbing materials can generally be divided into magnetic loss materials and dielectric loss materials. Traditional metal-based magnetic loss materials, such as ferrites and metal powders, have attracted much attention due to their large magnetic loss and strong absorption capacity in certain special frequency bands. However, their high density leads to high filling rate and easy agglomeration, and the existence of disadvantages such as impedance mismatch, narrow absorption band and poor corrosion resistance limits the application of ferromagnetic materials as high-performance absorbing materials. Traditional carbon-based dielectric loss materials have been widely reported due to their advantages such as low density, good thermal and chemical stability, and abundant carbon sources. However, traditional carbon materials are not suitable as absorbing materials alone due to their high dielectric loss. Doping heteroatoms in traditional carbon materials to introduce defects to produce dipole polarization to promote the material's absorption of electromagnetic waves or designing special structures to increase the absorption of electromagnetic wave energy has been proven to be an effective strategy for preparing innovative electromagnetic wave absorbing materials. For example, BP Liu et al. proposed nitrogen atom-doped and hollow metal organic framework-derived carbon materials in the title “Carbon nanocages with N-doped carbon inner shell and Co / N-doped carbon outer shell as electromagnetic wave absorption materials”, Chemical Engineering Journal, 2020, 381:122653. When the filling amount is 25wt%, this material has good electromagnetic wave absorption performance; Li Huang et al. proposed “Microwave absorption enhancement of porous C@CoFe 2 O 4Nanocomposites derived from eggshell membrane”, Carbon, 2019, 143:507-516 published a porous C@CoFe 2 O 4 Nanocomposite materials, when loaded with 30wt% in a paraffin matrix, have good electromagnetic wave absorption performance. The above examples improve the wave absorption performance of single carbon materials by introducing heteroatoms into carbon materials or designing special structures, but they all contain metal substances, and the obtained metal-containing composite wave absorbing materials have the disadvantages of high density and poor corrosion resistance, which cannot meet the requirements of new wave absorbing materials for "thin, light, wide and strong". [Summary of the invention]
[0004] [Technical issues to be solved]
[0005] The purpose of the present invention is to provide a carbon-based all-dielectric loss multi-component composite material.
[0006] The purpose of the present invention is to provide a method for preparing the carbon-based all-dielectric loss multi-component composite material.
[0007] [Technical solution]
[0008] The present invention is achieved through the following technical solutions.
[0009] The invention relates to a method for preparing a carbon-based full dielectric loss multi-component composite material.
[0010] The preparation steps of the preparation method are as follows:
[0011] A. Preparation of binary copolymer microspheres
[0012] Dissolve 4 to 8 parts by weight of acrylonitrile, 0.5 to 1.0 parts by weight of methacrylate monomer and 0.15 to 0.50 parts by weight of azobisisobutyronitrile initiator in 40 to 90 parts by weight of water, and then react for 3.0 to 3.5 hours at a temperature of 70 to 75° C. with stirring, and then centrifuge and separate using a centrifuge, and dry the collected solid product to obtain the binary copolymer microspheres;
[0013] B. Preparation of a mixture of amide compounds containing capsaicin functional structure
[0014] The monosaccharide is dissolved in a mixed solvent composed of ethanol and deionized water in a volume ratio of 1:1-2, and stirred using an intelligent temperature-controlled magnetic stirrer; then the binary copolymer microspheres obtained in step A and an equal weight of amide compounds containing capsaicin functional structure are added, and the ratio of their total weight to the weight of the monosaccharide is 0.1-5.0:1.0, and the intelligent temperature-controlled magnetic stirrer is continued to be used for stirring, and a solid mixture is obtained by suction filtration, and the solid mixture is washed 2-4 times with an ethanol aqueous solution with a concentration of 15-30% by volume and a deionized water washing liquid in a ratio of 1:50-100 of the solid mixture in grams to the washing liquid in milliliters, and the washed solid mixture is then dried in an oven, so as to obtain a solid powder of the mixture containing capsaicin functional structure amide compounds, binary copolymer microspheres and monosaccharide;
[0015] C. Carbonization
[0016] The solid powder obtained in step B and contained in the crucible is placed in a vacuum tube furnace, and a nitrogen or argon protective gas is passed through the vacuum tube furnace at a flow rate of 200 to 300 mL / min, and the air in the vacuum tube furnace is discharged out of the furnace, and then heated to 300°C at a heating rate of 1 to 2°C / min, and maintained at this temperature for 0.8 to 1.2 hours, and then heated to 700°C at a heating rate of 3 to 5°C / min, and carbonized at this temperature for 0.8 to 1.4 hours; after carbonization, the vacuum tube furnace is cooled to a temperature below 40°C, thereby obtaining the carbon-based all-dielectric loss multi-component composite material.
[0017] According to a preferred embodiment of the present invention, in step A, the methacrylate monomer is methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate or isobutyl methacrylate.
[0018] According to another preferred embodiment of the present invention, in step A, the obtained reactants are centrifuged using a centrifuge at a rotation speed of 8000 to 12000 rpm for 1 to 3 min.
[0019] According to another preferred embodiment of the present invention, in step A, the diameter of the binary copolymer microspheres is 300-420 nm.
[0020] According to another preferred embodiment of the present invention, in step B, the capsaicin functional structure amide compound is selected from 2,5-dimethylphenol derivatives, 3,4-dimethylphenol derivatives, 3,5-dimethylphenol derivatives, gallic acid derivatives, propyl gallate derivatives, methyl gallate derivatives, ethyl gallate derivatives, eugenol derivatives, 2,3,5-trimethylphenol derivatives or 2,3,6-trimethylphenol derivatives.
[0021] According to another preferred embodiment of the present invention, in step B, the stirring is performed using an intelligent temperature-controlled magnetic stirrer at a rotation speed of 600 to 1000 rpm for 45 to 75 minutes.
[0022] According to another preferred embodiment of the present invention, in step A and step B, the drying process is carried out in an oven at a temperature of 50 to 60° C. for 24 to 36 hours.
[0023] The present invention also relates to a carbon-based full dielectric loss multi-component composite material prepared by the preparation method. The carbon-based full dielectric loss multi-component composite material is composed of C, N and O elements in a weight ratio of 85-88:5-9:4-7.
[0024] According to a preferred embodiment of the present invention, the binary copolymer microspheres are attached to or embedded in a carbon sheet formed by an amide compound containing a capsaicin functional structure and a monosaccharide.
[0025] According to another preferred embodiment of the present invention, the carbon-based all-dielectric lossy multi-component composite material has an absorption rate of more than 90% for electromagnetic waves in the frequency band of 2 to 40 GHz.
[0026] The present invention will be described in more detail below.
[0027] The present invention relates to a carbon-based all-dielectric loss multi-component composite material. The multi-component composite material is composed of organic small molecule capsaicin functional structure amide compounds, monosaccharides and binary copolymer microspheres mainly composed of acrylonitrile. The multi-component composite material contains only C, N, and O elements. The binary copolymer microspheres are attached to or partially embedded in a carbon sheet composed of organic small molecule capsaicin functional structure amide compounds and monosaccharides. The diameter of the binary copolymer microspheres is 300 to 420 nm.
[0028] The multi-composite material prepared by using organic small molecule capsaicin-containing functional structure amide compounds to replace metals can not only effectively solve the shortcomings of current magnetic metal-based absorbing materials such as high density, narrow absorbing band and poor corrosion resistance, but also the capsaicin-containing functional structure amide compounds have the same good thermal stability and environmental protection as capsaicin, so that the prepared multi-composite material can retain the characteristics of light weight and high chemical stability of traditional carbon materials. The aromatic rings and amide groups (N and O atoms) in the structure of the amide compounds containing capsaicin functional structure can serve as polarization centers after carbonization, causing dipole polarization and inducing polarization resonance in the high-frequency region. Heteroatoms can also adjust the electronic state density of the carbon material, thereby improving the electrical conductivity of the material, which is beneficial for the material to convert electromagnetic energy into thermal energy. The binary copolymer microspheres are attached to or partially embedded in the carbon sheets composed of organic small molecule amide compounds containing capsaicin functional structure and monosaccharides, which provides a rich heterogeneous interface and can induce interface polarization, which is beneficial for electromagnetic waves to be reflected and scattered multiple times inside the material to promote electromagnetic wave attenuation. This greatly promotes the absorption of electromagnetic waves, so that the prepared electromagnetic absorber has excellent electromagnetic wave absorption performance, meeting the requirements of new absorbing materials for "thin, light, wide and strong".
[0029] The invention relates to a method for preparing a carbon-based full dielectric loss multi-component composite material.
[0030] The preparation steps of the preparation method are as follows:
[0031] A. Preparation of binary copolymer microspheres
[0032] Dissolve 4 to 8 parts by weight of acrylonitrile, 0.5 to 1.0 parts by weight of methacrylate monomer and 0.15 to 0.50 parts by weight of azobisisobutyronitrile initiator in 40 to 90 parts by weight of water, and then react for 3.0 to 3.5 hours at a temperature of 70 to 75° C. with stirring, and then centrifuge and separate using a centrifuge, and dry the collected solid product to obtain the binary copolymer microspheres;
[0033] The method for preparing binary copolymer microspheres of the present invention is designed with reference to the method for preparing copolymer microspheres by a soap-free emulsion method described by D. Wang et al. in the title "Preparation and Electromagnetic-wave-absorption properties of N,O-doped PMMA&DVB&AN carbon microspheres with porous hollow structures", Chemical Engineering Journal, 2023, 456:140987.
[0034] According to the present invention, the main role of acrylonitrile in preparing binary copolymer microspheres is to provide a nitrogen-rich monomer that can undergo free radical polymerization with other monomers.
[0035] The acrylonitrile used in the present invention is a product currently sold on the market, such as a product sold by Sinopharm Chemical Reagent Co., Ltd. under the trade name acrylonitrile.
[0036] The main function of methacrylate monomers in the preparation of binary copolymer microspheres is to provide a crosslinking agent for copolymerization reactions.
[0037] The methacrylate monomer used in the present invention is methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate or isobutyl methacrylate, which are all products currently sold on the market, such as the product sold by Sinopharm Chemical Reagent Co., Ltd. under the trade name of methyl methacrylate.
[0038] The main function of azobisisobutyronitrile initiator in the preparation of binary copolymer microspheres is to promote the cross-linking copolymerization reaction of different monomers.
[0039] The azobisisobutyronitrile initiator used in the present invention is a product currently sold on the market, for example, a product sold by Tianjin Damao Chemical Co., Ltd. under the trade name of azobisisobutyronitrile.
[0040] In the present invention, when the amount of methacrylate monomer, azobisisobutyronitrile and water is within the range, if the amount of acrylonitrile is less than 4 parts by weight, the particle size of the prepared binary copolymer microspheres is too small and the yield is low; if the amount of acrylonitrile is more than 8 parts by weight, the particle size of the prepared binary copolymer microspheres is too large and agglomerates; therefore, it is reasonable to use 4 to 8 parts by weight of acrylonitrile;
[0041] When the amount of acrylonitrile, azobisisobutyronitrile and water is within the above range, if the amount of methacrylate monomer is less than 0.5 parts by weight, the microspheres cannot be well formed; if the amount of methacrylate monomer is more than 1.0 parts by weight, the prepared binary copolymer microspheres agglomerate; therefore, the amount of methacrylate monomer is appropriately 0.5 to 1.0 parts by weight;
[0042] When the amount of acrylonitrile, methacrylate monomer and water is within the above range, if the amount of azobisisobutyronitrile is less than 0.15 parts by weight, the reaction is not thorough and the copolymerization into spheres cannot be well performed; if the amount of azobisisobutyronitrile is higher than 0.50 parts by weight, the reaction rate is too fast and the copolymer microspheres agglomerate over a large area; therefore, the amount of azobisisobutyronitrile is appropriately 0.15 to 0.50 parts by weight;
[0043] When the amount of acrylonitrile, methacrylate monomers and azobisisobutyronitrile is within the above range, if the amount of water is less than 40 parts by weight, the monomer concentration will be too high and the prepared binary copolymer microspheres will agglomerate; if the amount of water is more than 90 parts by weight, the particle size of the prepared binary copolymer microspheres will be uneven; therefore, it is desirable that the amount of water is 40 to 90 parts by weight;
[0044] According to the present invention, acrylonitrile, methacrylate monomers and azobisisobutyronitrile are reacted in water at a temperature of 70 to 75°C with stirring for 3.0 to 3.5 hours. When the reaction time is within the range, if the reaction temperature is lower than 70°C, the particle size of the prepared binary copolymer microspheres is uneven; if the reaction temperature is higher than 75°C, the prepared binary copolymer microspheres agglomerate; therefore, a reaction temperature of 70 to 75°C is appropriate; when the reaction temperature is within the range, if the reaction time is shorter than 3.0 hours, the reaction is not thorough; if the reaction time is longer than 3.5 hours, the prepared binary copolymer microspheres agglomerate; therefore, a reaction time of 3.0 to 3.5 hours is appropriate;
[0045] In this step, the obtained reactants are centrifuged at 8000-12000 rpm for 1-3 min using a centrifuge. The centrifuge used in the present invention is a product currently sold on the market, such as a centrifuge sold by Xiangyi Company under the trade name of high-speed desktop centrifuge.
[0046] According to the present invention, the collected solid product is dried in an oven at 50-60° C. for 24-36 hours. According to the atmospheric pressure drying standard analysis method, the water content of the dried solid product obtained by the drying step is less than 1% by weight.
[0047] The oven used in the drying process of the present invention is a product currently sold on the market, such as a product sold under the trade name of an electric constant temperature blast drying oven by Shanghai Senxin Experimental Instrument Co., Ltd. The subsequent step B also uses the same oven, so it will not be described in detail below.
[0048] According to the method of measuring microsphere diameter using Photoshop software, the diameter of the binary copolymer microspheres obtained in this step is 300-420 nm.
[0049] B. Preparation of a mixture of amide compounds containing capsaicin functional structure
[0050] The monosaccharide is dissolved in a mixed solvent composed of ethanol and deionized water in a volume ratio of 1:1-2, and stirred using an intelligent temperature-controlled magnetic stirrer; then the binary copolymer microspheres obtained in step A and an equal weight of amide compounds containing capsaicin functional structure are added, and the ratio of their total weight to the weight of the monosaccharide is 0.1-5.0:1.0, and the intelligent temperature-controlled magnetic stirrer is continued to be used for stirring, and a solid mixture is obtained by suction filtration, and the solid mixture is washed 2-4 times with an ethanol aqueous solution with a concentration of 15-30% by volume and a deionized water washing liquid in a ratio of 1:50-100 of the solid mixture in grams to the washing liquid in milliliters, and the washed solid mixture is then dried in an oven, so as to obtain a solid powder of the mixture containing capsaicin functional structure amide compounds, binary copolymer microspheres and monosaccharide;
[0051] According to the present invention, the capsaicin functional structure-containing amide compounds are selected from 2,5-dimethylphenol derivatives, 3,4-dimethylphenol derivatives, 3,5-dimethylphenol derivatives, gallic acid derivatives, propyl gallate derivatives, methyl gallate derivatives, ethyl gallate derivatives, eugenol derivatives, 2,3,5-trimethylphenol derivatives or 2,3,6-trimethylphenol derivatives, and these compounds are synthesized according to the synthesis methods described in CN 201410187252.X, invention name "Monofunctional acrylamide compounds with capsaicin-like functional structures, preparation methods and applications thereof" and CN 201410187148.0, invention name "Multifunctional acrylamide compounds containing capsaicin-like functional structures, preparation methods and applications thereof".
[0052] In the present invention, the monosaccharide is a product currently sold on the market, such as the monosaccharide sold by Shandong Qilu Biotechnology under the trade names of glucosamine, sucrose, and maltose.
[0053] In this step, the main purpose of using an intelligent temperature-controlled magnetic stirrer for stirring is to allow the monosaccharide, binary copolymer microspheres and the capsaicin-containing functional structure amide compounds to fully dissolve and cross-link.
[0054] Use an intelligent temperature-controlled magnetic stirrer to stir at a speed of 600 to 1000 rpm for 45 to 75 minutes. When the stirring time is within the range, if the stirring speed of the stirrer is lower than 600 rpm, it takes a long time for the monosaccharide, binary copolymer microspheres and the capsaicin functional structure amide compounds to dissolve each other; if the stirring speed of the stirrer is higher than 1000 rpm, the solvent evaporates quickly, resulting in waste; therefore, a stirring speed of 600 to 1000 rpm is appropriate; when the stirring speed of the stirrer is within the range, if the stirring time is shorter than 45 minutes, the mutual dissolution is insufficient; if the stirring time is longer than 75 minutes, the solvent evaporates and wastes; therefore, a stirring time of 45 to 75 minutes is appropriate;
[0055] The intelligent temperature-controlled magnetic stirrer used in the present invention is an instrument currently sold on the market, for example, an instrument sold by Hunan Powder Equipment Research Institute Co., Ltd. as an intelligent temperature-controlled magnetic stirrer.
[0056] In this step, the equipment used for filtration is a water flow filtration device with a Buchner funnel, which is a product currently sold on the market, such as the product sold by Qi Yu Industrial (Shanghai) Co., Ltd. under the trade name of water flow vacuum pump.
[0057] In this step, the solid mixture obtained by filtration is washed with an ethanol aqueous solution having a concentration of 15 to 30% by volume in order to remove unreacted capsaicin-containing functional structure amide compounds, and then washed with deionized water in order to remove unreacted binary copolymer microspheres and monosaccharides.
[0058] In this step, it is undesirable for the concentration of the ethanol-water washing liquid to exceed the range of 15-30% because it will cause a waste of ethanol;
[0059] According to the present invention, the washed solid product is dried in an oven at 50-60° C. for 24-36 hours. According to the atmospheric pressure drying standard analysis method, the water content of the dry solid powder product obtained by the drying step is less than 1% by weight.
[0060] C. Carbonization
[0061] The solid powder obtained in step B and contained in the crucible is placed in a vacuum tube furnace, and a nitrogen or argon protective gas is passed through the vacuum tube furnace at a flow rate of 200 to 300 mL / min, and the air in the vacuum tube furnace is discharged out of the furnace, and then heated to 300°C at a heating rate of 1 to 2°C / min, and maintained at this temperature for 0.8 to 1.2 hours, and then heated to 700°C at a heating rate of 3 to 5°C / min, and carbonized at this temperature for 0.8 to 1.4 hours; after carbonization, the vacuum tube furnace is cooled to a temperature below 40°C, thereby obtaining the carbon-based all-dielectric loss multi-component composite material.
[0062] In this step, the solid powder obtained in step B is treated with an inert protective gas in a vacuum tube furnace to protect the organic small molecule capsaicin functional structure amide compounds, binary copolymer microspheres and monosaccharides from being oxidized. The inert protective gas used in the present invention is nitrogen or argon inert gas.
[0063] According to the oxygen probe installed on the furnace, the oxygen content in the vacuum tube furnace using inert protective gas to exhaust air should be less than 2%.
[0064] In this step, the solid powder in the vacuum tube furnace with air exhausted is heated to a temperature of 300°C at a heating rate of 1-2°C / min and maintained at this temperature for 0.8-1.2h. The purpose of this heating step is to maintain the stability of the mixture structure.
[0065] Next, the temperature is increased to 700°C at a rate of 3 to 5°C / min, and carbonized at this temperature for 0.8 to 1.4 hours. The purpose of this heating step is to obtain a carbon-based all-dielectric loss multi-composite material during the pyrolysis and carbonization process. When the carbonization temperature and the carbonization time are within the range, if the temperature increase rate is lower than 3°C / min, inert gas is wasted. If the temperature increase rate is higher than 5°C / min, the multi-composite material cannot be fully pyrolyzed and carbonized. Therefore, a temperature increase rate of 3 to 5°C / min is appropriate. When the temperature increase rate is within the range, if the carbonization time is shorter than 0.8h, the multi-composite material cannot be fully pyrolyzed and carbonized. If the carbonization time is longer than 1.4h, inert gas is wasted. Therefore, a carbonization time of 0.8 to 1.4h is desirable.
[0066] The carbonized carbon-based all-dielectric loss multi-component composite material was characterized by electron microscopy under conventional conditions using a scanning electron microscope sold by Japan's HITACHI Corporation under the trade name S-4800 scanning electron microscope. The analysis results are listed in the attached Figure 1 a-1c.
[0067] The present invention also relates to a carbon-based full dielectric loss multi-component composite material prepared by the preparation method. The carbon-based full dielectric loss multi-component composite material is composed of C, N and O elements in a weight ratio of 85-88:5-9:4-7;
[0068] The carbonization product was observed using an S-4800 scanning electron microscope and an X-ray photoelectron spectrometer sold by Thermo Corporation under the trade name X-ray photoelectron spectrometer. The results showed that the carbon-based all-dielectric loss multi-component composite material is composed of C, N and O elements in a weight ratio of 85-88:5-9:4-7.
[0069] The carbonized product was observed using a FEI Technai F20 field emission transmission electron microscope, and the results showed that the binary copolymer microspheres were attached to or embedded in the carbon sheet formed by the capsaicin functional structure amide compound and monosaccharide.
[0070] The carbon-based all-dielectric loss multi-component composite material of the invention has an absorption rate of more than 90% for electromagnetic waves in the frequency band of 2 to 40 GHz.
[0071] The present invention uses a two-port vector network analyzer sold by Agilent under the trade name PNA Network Analyzer N5224A to test the electromagnetic performance parameters of the material at room temperature. According to the document Luo Kong, et al., titled "Flexible CNTs / CNF-WPU aerogel for smart electromagnetic wave absorbingwith tuning effective absorption bandwidth", "Carbon", 207, 2023, 13-22, the reflection loss of the carbon-based all-dielectric loss multi-composite material is calculated by transmission line theory. The carbide powder and paraffin obtained in step E are evenly mixed and pressed into concentric ring samples with an inner diameter of 3.04 mm, an outer diameter of 7.0 mm and a thickness of 2.5 mm using an existing mold press. The electromagnetic reflection loss of the sample in the frequency range of 2 to 40 GHz is calculated. To ensure the accuracy of the test results, the front and back sides of the concentric ring samples are tested more than twice. By the attached Figure 2 It can be seen that the minimum reflection loss of the composite material is -45.02dB at a frequency of 13.84GHz, and the corresponding effective bandwidth is 6.40GHz (11.28~17.68GHz); the minimum reflection loss is -29.88dB at a frequency of 25.99GHz and a sample matching thickness of 1.0mm, and the corresponding effective bandwidth is 3.06GHz (23.44-26.50GHz); the minimum reflection loss is -19.47dB at a frequency of 28.39GHz and a sample matching thickness of 1.0mm, and the corresponding effective bandwidth is 1.98GHz (26.74-28.72GHz).
[0072] [Beneficial Effects]
[0073] The beneficial effects of the present invention are:
[0074] This carbon-based all-dielectric lossy multi-composite material does not contain any metal substances, which effectively avoids the shortcomings of metal-based absorbing materials, such as high density, narrow absorbing bandwidth and poor corrosion resistance. In addition, the heteroatoms contained in this carbon-based all-dielectric lossy multi-composite material can produce dipole polarization and the rich heterogeneous interfaces can induce interface polarization, which greatly promotes the absorption of electromagnetic waves.
Brief Description of the Drawings
[0075] Figure 1 ab are scanning electron microscope (SEM) images of the carbon-based all-dielectric lossy multi-component composite materials prepared in Examples 1-4 and Figure 1 ef Transmission electron microscope (TEM) image of the carbon-based all-dielectric lossy multi-component composite material prepared in Example 1-2;
[0076] In the figure:
[0077] 1a-Example 1; 1b-Example 2; 1c-Example 3; 1d-Example 4; 1e-Example 1; 1f-Example 2;
[0078] Figure 2 This is a reflection loss diagram of the carbon-based all-dielectric lossy multi-component composite material prepared in Example 1 in the frequency range of 2 to 40 GHz;
[0079] In the figure:
[0080] 2a-Reflection loss diagram of the multi-component composite material of Example 1 in the frequency range of 2 to 18 GHz; 2b-Reflection loss diagram of the multi-component composite material of Example 1 in the frequency range of 18 to 26.5 GHz; 2c-Reflection loss diagram of the multi-component composite material of Example 1 in the frequency range of 26.5 to 40 GHz. [Specific implementation method]
[0081] The present invention will be better understood through the following examples.
[0082] Example 1: Preparation of the carbon-based all-dielectric loss multi-component composite material of the present invention
[0083] The implementation steps of this embodiment are as follows:
[0084] A. Preparation of binary copolymer microspheres
[0085] 6 parts by weight of acrylonitrile, 0.5 parts by weight of methyl methacrylate methacrylate monomer and 0.38 parts by weight of azobisisobutyronitrile initiator are dissolved in 55 parts by weight of water, followed by reaction at 75°C with stirring for 3.0 hours, and then centrifuged at 8000 rpm for 3 minutes using a centrifuge. The collected solid product is dried in an oven at 58°C for 28 hours to obtain binary copolymer microspheres with a water content of 0.5% by weight. According to the method described in the specification of the present application, the diameter of the binary copolymer microspheres is 300 to 420 nm.
[0086] B. Preparation of a mixture of amide compounds containing capsaicin functional structure
[0087] Dissolve glucosamine monosaccharide in a mixed solvent composed of ethanol and deionized water in a volume ratio of 1:1.8, and then use an intelligent temperature-controlled magnetic stirrer to stir for 75 minutes at a speed of 730rpm; then add the binary copolymer microspheres obtained in step A and an equal weight of 2,5-dimethylphenol derivatives containing capsaicin functional structure amide compounds, the total weight of which is 0.1:1.0 to the weight of glucosamine monosaccharide, continue to use an intelligent temperature-controlled magnetic stirrer to stir for 45 minutes at a speed of 1000rpm, and filter to obtain a solid mixture, according to the ratio of solid mixture in grams to washing liquid in milliliters of 1:80, successively use ethanol aqueous solution with a concentration of 20% by volume and deionized water washing liquid for three times, and then dry the washed solid mixture in an oven at a temperature of 60°C for 24 hours, so as to obtain a solid powder of capsaicin functional structure amide compounds, binary copolymer microspheres and monosaccharide mixture; according to the standard analytical method described in the specification of this application, the water content of the dried solid powder product is 0.5% by weight.
[0088] C. Carbonization
[0089] The solid powder obtained in step B and contained in the crucible is placed in a vacuum tube furnace, and nitrogen protective gas is passed through the vacuum tube furnace at a flow rate of 250 mL / min to discharge the air in the vacuum tube furnace out of the furnace, and then heated to 300°C at a heating rate of 1°C / min and maintained at this temperature for 1.0 h, and then heated to 700°C at a heating rate of 4°C / min and carbonized at this temperature for 1.0 h; after carbonization, the vacuum tube furnace is cooled to a temperature below 40°C, thereby obtaining the carbon-based all-dielectric loss multi-composite material.
[0090] The carbonized carbon-based all-dielectric loss multi-component composite material was characterized by scanning electron microscopy under conventional conditions. The analysis results are listed in the attached Figure 1 a.
[0091] According to the method described in the specification of the present application, the carbon-based all-dielectric loss multi-component composite material prepared in this embodiment is composed of C, N and O elements in a weight ratio of 85:8:4.
[0092] The method described in the specification of the present application is used to detect and determine that the binary copolymer microspheres are attached to or embedded in the carbon sheet formed by the amide compound containing the capsaicin functional structure and the monosaccharide.
[0093] Example 2: Preparation of the carbon-based all-dielectric loss multi-component composite material of the present invention
[0094] The implementation steps of this embodiment are as follows:
[0095] A. Preparation of binary copolymer microspheres
[0096] 4 parts by weight of acrylonitrile, 0.6 parts by weight of ethyl methacrylate methacrylate monomer and 0.15 parts by weight of azobisisobutyronitrile initiator are dissolved in 72 parts by weight of water, followed by reaction at 70°C with stirring for 3.5 hours, and then centrifuged at 9000 rpm for 2 minutes using a centrifuge. The collected solid product is dried in an oven at 50°C for 36 hours to obtain binary copolymer microspheres with a water content of 0.4% by weight. According to the method described in the specification of the present application, the diameter of the binary copolymer microspheres is 300 to 420 nm.
[0097] B. Preparation of a mixture of amide compounds containing capsaicin functional structure
[0098] Sucrose monosaccharide is dissolved in a mixed solvent composed of ethanol and deionized water in a volume ratio of 1:1.0, and then stirred for 65 minutes using an intelligent temperature-controlled magnetic stirrer at a speed of 1000 rpm; then the binary copolymer microspheres obtained in step A and an equal weight portion of gallic acid propyl ester derivative containing capsaicin functional structure amide compounds are added, and the ratio of their total weight to the weight of sucrose monosaccharide is 1.6:1.0, and the intelligent temperature-controlled magnetic stirrer is continued to be stirred for 75 minutes at a speed of 600 rpm, and a solid mixture is obtained by suction filtration. According to the ratio of the solid mixture in grams to the washing liquid in milliliters of 1:100, it is washed twice with a 25% ethanol aqueous solution and a deionized water washing liquid, and the washed solid mixture is then dried in an oven at a temperature of 50°C for 36 hours to obtain a solid powder of a mixture of capsaicin functional structure amide compounds, binary copolymer microspheres and monosaccharides; according to the standard analytical method described in the specification of this application, the water content of the dried solid powder product is 0.4% by weight.
[0099] C. Carbonization
[0100] The solid powder obtained in step B and contained in the crucible is placed in a vacuum tube furnace, and argon protective gas is passed through the vacuum tube furnace at a flow rate of 200 mL / min, and the air in the vacuum tube furnace is discharged out of the furnace, and then heated to 300°C at a heating rate of 2°C / min, and maintained at this temperature for 0.8h, and then heated to 700°C at a heating rate of 3°C / min, and carbonized at this temperature for 1.2h; after carbonization, the vacuum tube furnace is cooled to a temperature below 40°C, thereby obtaining the carbon-based all-dielectric loss multi-composite material.
[0101] The carbonized carbon-based all-dielectric loss multi-component composite material was characterized by scanning electron microscopy under conventional conditions. The analysis results are listed in the attached Figure 1 b.
[0102] According to the method described in the specification of the present application, the carbon-based all-dielectric loss multi-component composite material prepared in this embodiment is composed of C, N and O elements in a weight ratio of 86:5:7.
[0103] The method described in the specification of the present application is used to detect and determine that the binary copolymer microspheres are attached to or embedded in the carbon sheet formed by the amide compound containing the capsaicin functional structure and the monosaccharide.
[0104] Example 3: Preparation of the carbon-based all-dielectric loss multi-component composite material of the present invention
[0105] The implementation steps of this embodiment are as follows:
[0106] A. Preparation of binary copolymer microspheres
[0107] 5 parts by weight of acrylonitrile, 1.0 parts by weight of propyl methacrylate methacrylate monomer and 0.26 parts by weight of azobisisobutyronitrile initiator are dissolved in 90 parts by weight of water, followed by reaction at 72°C with stirring for 3.4 hours, and then centrifuged at 12000 rpm for 1 minute using a centrifuge, and the collected solid product is dried in an oven at 60°C for 24 hours to obtain binary copolymer microspheres with a water content of 0.6% by weight; according to the method described in the specification of the present application, the diameter of the binary copolymer microspheres is 300 to 420 nm.
[0108] B. Preparation of a mixture of amide compounds containing capsaicin functional structure
[0109] The maltose monosaccharide is dissolved in a mixed solvent composed of ethanol and deionized water in a volume ratio of 1:1.4, and then stirred for 45 minutes using an intelligent temperature-controlled magnetic stirrer at a speed of 600 rpm; then the binary copolymer microspheres obtained in step A and an equal weight portion of eugenol derivatives containing capsaicin functional structure amide compounds are added, and the ratio of their total weight to the weight of maltose monosaccharide is 3.4:1.0, and the intelligent temperature-controlled magnetic stirrer is continued to be stirred at a speed of 730 rpm for 65 minutes, and a solid mixture is obtained by suction filtration. According to the ratio of the solid mixture in grams to the washing liquid in milliliters of 1:50, it is washed 4 times with a 15% ethanol aqueous solution and a deionized water washing liquid, and the washed solid mixture is then dried in an oven at a temperature of 53°C for 32 hours to obtain a solid powder of a mixture of capsaicin functional structure amide compounds, binary copolymer microspheres and monosaccharides; according to the standard analytical method described in the specification of this application, the water content of the dried solid powder product is 0.4% by weight.
[0110] C. Carbonization
[0111] The solid powder obtained in step B and contained in the crucible is placed in a vacuum tube furnace, and nitrogen protective gas is passed through the vacuum tube furnace at a flow rate of 300 mL / min to discharge the air in the vacuum tube furnace out of the furnace, and then heated to 300°C at a heating rate of 1°C / min and maintained at this temperature for 1.2 hours, and then heated to 700°C at a heating rate of 5°C / min and carbonized at this temperature for 1.4 hours; after carbonization, the vacuum tube furnace is cooled to a temperature below 40°C, thereby obtaining the carbon-based all-dielectric loss multi-composite material.
[0112] The carbonized carbon-based all-dielectric loss multi-component composite material was characterized by scanning electron microscopy under conventional conditions. The analysis results are listed in the attached Figure 1 c.
[0113] According to the method described in the specification of the present application, the carbon-based all-dielectric loss multi-component composite material prepared in this embodiment is composed of C, N and O elements in a weight ratio of 88:7:6.
[0114] The method described in the specification of the present application is used to detect and determine that the binary copolymer microspheres are attached to or embedded in the carbon sheet formed by the amide compound containing the capsaicin functional structure and the monosaccharide.
[0115] Example 4: Preparation of the carbon-based all-dielectric loss multi-component composite material of the present invention
[0116] The implementation steps of this embodiment are as follows:
[0117] A. Preparation of binary copolymer microspheres
[0118] 8 parts by weight of acrylonitrile, 0.8 parts by weight of n-butyl methacrylate methacrylate monomer and 0.50 parts by weight of azobisisobutyronitrile initiator are dissolved in 40 parts by weight of water, followed by reaction at 74°C with stirring for 3.2 hours, and then centrifuged at 9000 rpm for 2 minutes using a centrifuge. The collected solid product is dried in an oven at 54°C for 32 hours to obtain binary copolymer microspheres with a water content of 0.2% by weight. According to the method described in the specification of the present application, the diameter of the binary copolymer microspheres is 300 to 420 nm.
[0119] B. Preparation of a mixture of amide compounds containing capsaicin functional structure
[0120] Dissolve glucosamine monosaccharide in a mixed solvent composed of ethanol and deionized water in a volume ratio of 1:2.0, and then use an intelligent temperature-controlled magnetic stirrer to stir at a speed of 860 rpm for 55 minutes; then add the binary copolymer microspheres obtained in step A and an equal weight portion of 2,3,5-trimethylphenol derivative containing capsaicin functional structure amide compounds, the total weight of which is 5.0:1.0 to the weight of glucosamine monosaccharide, and continue to use an intelligent temperature-controlled magnetic stirrer to stir at a speed of 860 rpm for 5 minutes. 5min, filter to obtain a solid mixture, wash it three times with 30% ethanol aqueous solution and deionized water washing solution in a ratio of 1:65 of solid mixture in grams to washing solution in milliliters, dry it in an oven at 57°C for 28h, and obtain a solid powder of a mixture of amide compounds with capsaicin functional structure, binary copolymer microspheres and monosaccharides; according to the standard analytical method described in the specification of the present application, the water content of the dried solid powder product is 0.4% by weight.
[0121] C. Carbonization
[0122] The solid powder obtained in step B and contained in the crucible is placed in a vacuum tube furnace, and argon protective gas is passed through the vacuum tube furnace at a flow rate of 250 mL / min, and the air in the vacuum tube furnace is discharged out of the furnace, and then heated to 300°C at a heating rate of 2°C / min, and maintained at this temperature for 1.0 h, and then heated to 700°C at a heating rate of 4°C / min, and carbonized at this temperature for 0.8 h; after carbonization, the vacuum tube furnace is cooled to a temperature below 40°C, thereby obtaining the carbon-based all-dielectric loss multi-composite material.
[0123] The carbonized carbon-based all-dielectric loss multi-component composite material was characterized by scanning electron microscopy under conventional conditions. The analysis results are listed in the attached Figure 1 d.
[0124] According to the method described in the specification of the present application, the carbon-based all-dielectric loss multi-component composite material prepared in this embodiment is composed of C, N and O elements in a weight ratio of 86:9:5.
[0125] The method described in the specification of the present application is used to detect and determine that the binary copolymer microspheres are attached to or embedded in the carbon sheet formed by the amide compound containing the capsaicin functional structure and the monosaccharide.
[0126] Application Example 1: Application of the carbon-based all-dielectric loss multi-component composite material of the present invention in absorbing electromagnetic waves
[0127] The implementation method of this application example is as follows:
[0128] The carbon-based all-dielectric loss multi-component composite material powder prepared in Example 1 was evenly mixed with paraffin in a weight ratio of 1:7, and the mixture was pressed into concentric circular ring samples with an inner diameter of 3.04 mm, an outer diameter of 7.0 mm and a thickness of 2.5 mm using a mold press sold by Tianjin Jinfulun Technology Co., Ltd. under the trade name XYM-H ring precision mold.
[0129] The electromagnetic performance parameters of the concentric ring sample were tested at room temperature using a two-port vector network analyzer sold by Agilent under the trade name PNA Network Analyzer N5224A. The reflection loss of the carbon-based all-dielectric loss multi-component composite material in the frequency range of 2 to 40 GHz was calculated using transmission line theory according to the method described in the specification of this application. The results are listed in the attached Figure 2 , including Figure 2 a is the reflection loss of the carbon-based all-dielectric lossy multi-component composite material in the frequency range of 2 to 18 GHz; Figure 2 b is the reflection loss of the carbon-based all-dielectric lossy multi-component composite material in the frequency range of 18 to 26.5 GHz; Figure 2 c is the reflection loss of the carbon-based all-dielectric lossy multi-component composite material in the frequency range of 26.5 to 40 GHz.
[0130] To ensure the accuracy of the test results, the front and back sides of the concentric ring samples were tested more than twice. Figure 2 It can be seen that the minimum reflection loss of the carbon-based all-dielectric lossy multi-composite material at a frequency of 13.84 GHz is -45.02 dB, and the corresponding effective bandwidth is 6.40 GHz (11.28-17.68 GHz); the minimum reflection loss at a frequency of 25.99 GHz and a sample matching thickness of 1.0 mm is -29.88 dB, and the corresponding effective bandwidth is 3.06 GHz (23.44-26.50 GHz); the minimum reflection loss at a frequency of 28.39 GHz and a sample matching thickness of 1.0 mm is -19.47 dB, and the corresponding effective bandwidth is 1.98 GHz (26.74-28.72 GHz). This shows that the carbon-based all-dielectric lossy multi-composite material absorbs more than 90% of electromagnetic waves in the 2-40 GHz frequency band, and has excellent electromagnetic wave absorption performance.
[0131] The carbon-based all-dielectric lossy multi-component composite materials prepared in Example 2-4 were also tested for the same electromagnetic performance parameters, and the reflection loss graphs obtained were similar to those in the attached figure. Figure 2 are consistent, indicating that these carbon-based all-dielectric loss multi-composite materials also have excellent electromagnetic wave absorption performance.
Claims
1. A method for preparing a carbon-based all-dielectric loss multi-component composite material, characterized in that The preparation steps of the preparation method are as follows: A. Preparation of binary copolymer microspheres Dissolve 4 to 8 parts by weight of acrylonitrile, 0.5 to 1.0 parts by weight of methacrylate monomer and 0.15 to 0.50 parts by weight of azobisisobutyronitrile initiator in 40 to 90 parts by weight of water, and then react for 3.0 to 3.5 hours at a temperature of 70 to 75° C. with stirring, and then centrifuge and separate using a centrifuge, and dry the collected solid product to obtain the binary copolymer microspheres; B. Preparation of a mixture of amide compounds containing capsaicin functional structure The monosaccharide is dissolved in a mixed solvent composed of ethanol and deionized water in a volume ratio of 1:1-2, and stirred using an intelligent temperature-controlled magnetic stirrer; then the binary copolymer microspheres obtained in step A and an equal weight of amide compounds containing capsaicin functional structure are added, and the ratio of their total weight to the weight of the monosaccharide is 0.1-5.0:1.0, and the intelligent temperature-controlled magnetic stirrer is continued to be used for stirring, and a solid mixture is obtained by suction filtration, and the solid mixture is washed 2-4 times with an ethanol aqueous solution with a concentration of 15-30% by volume and a deionized water washing liquid in a ratio of 1:50-100 of the solid mixture in grams to the washing liquid in milliliters, and the washed solid mixture is then dried in an oven, so as to obtain a solid powder of the mixture containing capsaicin functional structure amide compounds, binary copolymer microspheres and monosaccharide; C. Carbonization The solid powder obtained in step B and contained in the crucible is placed in a vacuum tube furnace, and a nitrogen or argon protective gas is passed through the vacuum tube furnace at a flow rate of 200 to 300 mL / min, and the air in the vacuum tube furnace is discharged out of the furnace, and then heated to 300°C at a heating rate of 1 to 2°C / min, and maintained at this temperature for 0.8 to 1.2 hours, and then heated to 700°C at a heating rate of 3 to 5°C / min, and carbonized at this temperature for 0.8 to 1.4 hours; after carbonization, the vacuum tube furnace is cooled to a temperature below 40°C, thereby obtaining the carbon-based all-dielectric loss multi-component composite material.
2. The preparation method according to claim 1, characterized in that In step A, the methacrylate monomer is methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate or isobutyl methacrylate.
3. The preparation method according to claim 1, characterized in that In step A, the obtained reactant is centrifuged at a rotation speed of 8000 to 12000 rpm for 1 to 3 minutes using a centrifuge.
4. The preparation method according to claim 1, characterized in that In step A, the diameter of the binary copolymer microspheres is 300-420 nm.
5. The preparation method according to claim 1, characterized in that In step B, the capsaicin functional structure amide compound is selected from 2,5-dimethylphenol derivatives, 3,4-dimethylphenol derivatives, 3,5-dimethylphenol derivatives, gallic acid derivatives, propyl gallate derivatives, methyl gallate derivatives, ethyl gallate derivatives, eugenol derivatives, 2,3,5-trimethylphenol derivatives or 2,3,6-trimethylphenol derivatives.
6. The preparation method according to claim 1, characterized in that In step B, the stirring is performed using an intelligent temperature-controlled magnetic stirrer at a rotation speed of 600 to 1000 rpm for 45 to 75 minutes.
7. The preparation method according to claim 1, characterized in that In step A and step B, the drying process is carried out in an oven at a temperature of 50 to 60° C. for 24 to 36 hours.
8. The carbon-based all-dielectric loss multi-component composite material prepared by the preparation method according to any one of claims 1 to 7, characterized in that It is composed of C, N and O elements in a weight ratio of 85-88:5-9:4-7.
9. The carbon-based all-dielectric loss multicomponent composite material according to claim 8, characterized in that The binary copolymer microspheres are attached to or embedded in a carbon sheet formed by an amide compound containing a capsaicin functional structure and monosaccharide.
10. The carbon-based all-dielectric loss multi-component composite material according to claim 8, characterized in that The carbon-based all-dielectric loss multi-component composite material has an absorption rate of more than 90% for electromagnetic waves in the 2-40 GHz frequency band.
Citation Information
Patent Citations
Monofunctional acrylamide compound with capsaicinoid functional structure and preparation method and application thereof
CN103951576A
Multifunctional acrylamide compound containing capsaicin-like functional structure and preparation method and application thereof
CN103951578A
Core-shell carbon ball / carbon nanotube composite wave absorption material and preparation method
CN106883818A
Hydrate temperature-control energy-storage magnetic composite material and preparation method thereof
CN112592697A